Relaciones Bioclimáticas del trigo en los Monegros - Martí Ezpeleta, Alberto (Geographicalia, 2017)
By means the computation of the correlation coeficient between yields and the conthly values of the precipitation, the maximum temperatures ocurred during the wheat vegetative cycle, the bioclimatic environment at the Monegros area are analised. Thanks to that analysis the critical periods when the wheat have more sensibility to the environment factors are determined.